Vehicular Traffic Flow Model with Driver Aggresiveness Component in a Multilane Road - Kariuki, E; Kimathi, M; Abidha, M.G (Journal of Applied and Computational Mathematics, 2016)
In this study, we outline the Kerner’s 3-phase traffic flow theory, which states that traffic flow occurs in three phases and these are free flow, synchronized flow and wide moving jam phases. A macroscopic traffic flow model that is factoring driver aggressiveness is developed and its features discussed. By construction of the solution to the Riemann problem, the model is written in conservative form and solved numerically. Using the Godunov numerical method we go ahead to simulate traffic flow on a multilane road with a lane-drop bottleneck. The model is compared with the Aw-Rascle model and features of the model are shown to reproduce the features of a three phase traffic flow which the Aw-Rascle model cannot reproduce. It is also shown that the model respects aspects of traffic by responding to frontal stimuli only and it does not produce negative travel.
Keywords: Three phase traffic theory; Conservation law; Phase transition